Influence of Ethanol Amount During Washing on Deagglomeration of Co‐Precipitated Calcined Nanocrystalline 3 YSZ Powders. (25th July 2012) - Patil, Sharanabasappa B.; Jena, Ajay Kumar; Bhargava, Parag
Abstract : Influence of ethanol treatment of co‐precipitated yttrium–zirconium hydroxide on deagglomeration of calcined nano 3 YSZ powder was studied. Results indicated that the amount of ethanol used in washing the zirconium hydroxide precipitate had a significant impact on the calcined powder characteristics. Different ratios of ethanol to the water contained within the precipitate were used during washing and the calcined nano 3 YSZ powders were characterized in terms of BET specific surface area, tap density, pressure‐displacement behavior during powder compaction, nanoindentation of green compacts, green and sintered body microstructures. The results indicated that a minimum ethanol amount of 2–3 times that of water in the precipitate was required to achieve superior deagglomeration of the calcined nano YSZ powders. The powders obtained by washing with optimum ethanol amount resulted in high green density and sintered density of compacts.